The practice and administration of the Shari' ah in Nigeria: issues in constitutionalism (2015)
This paper focuses on the rich and long history of Shari'ah administration and practice in Nigeria with respect to the constitutional issues. It examines the place of the Shari'ah in the Nigerian Constitution, its scope and penalties. How does the Nigerian constitution conceive of the Shari'ah application? What is the scope of the Shari'ah according to the Nigerian Constitution and can it be expanded? Does the Shari'ah application contravene the Nigerian Constitution, especially on the issue of human rights and how are these constitutional issues in respect of the administration of the Shari 'ah being perceived by Christians and Muslims in Nigeria? These are the questions this paper seeks to answer.